P4-to-blockchain: A secure blockchain-enabled packet parser for software defined networking. Issue 88 (January 2020) - Yazdinejad, Abbas; Parizi, Reza M.; Dehghantanha, Ali; Choo, Kim-Kwang Raymond
Highlights: A secure blockchain-enabled packet parser for software defined networking. Implementation of blockchain-enabled packet parser architecture using FPGA. High programmability and flexibility, as well as attack resilience. Abstract: Security is one of the most challenging issues in software defined networking (SDN), and causes include the inability to detect the contents of the packets. In addition, file transferring to SDN is a potential attack vector that can be exploited at the network level. On the SDN data plane (i.e. the switch), packets are processed so that their behavior in the network can be determined. Packet parser (PP) acts as the main role of this operation on the switch. PP plays a very important role in identifying packets and supporting protocols and testing new ideas in SDN, which requires packet parsers on the data plane to provide the necessary flexibility and programmability. In recent times, cryptographic ledger technology (also referred to as Blockchain in the literature) has been applied to securely transfer transactions and files in the networks, mainly for crypto payments. In this paper, we propose a new packet parser architecture called Blockchain-enabled Packet Parser (BPP) based on the security characteristics of the blockchain and support for data processing functions with the description of Programming Protocol-Independent Packet Processors (P4) language that has the BPP-independent attribute of the protocol. In the proposed architecture, we provide a mathematical model based on a multivariate correlation approach for attack detection from the observed packet traffic. The implementation of BPP architecture is on Field Programmable Gate Array (FPGA), which is known for its higher processing speed, flexibility, and lower consumption resources. The result indicates that the proposed BPP is able to detect attacks and policy performed on the control plane in how to detect an attack from a packet structure efficiently. Furthermore, the impact of the bandwidth with and without the BPP in hardware environment is evaluated to demonstrate BPP's efficiency. Graphical abstract: Image, graphical abstract